A study of prescription pattern in the drug therapy of CSOM at a tertiary care hospital in eastern part of India - Sharma, Manuprita; Ray, Bidhan; Sahu, Ramesh Kumar; Raman, Santosh; Bagga, Rupali Verma (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Chronic suppurative otitis media (CSOM) is a perforated tympanic membrane with persistent drainage from the middle ear (i.e. lasting >6-12 weeks). A prospective study was undertaken to find out the baseline data on the prescribing pattern of drugs in the treatment of chronic suppurative otitis media. Methods: A cross-sectional observational study was conducted on 125 patients attending ENT OPD and microbiology laboratory of a tertiary care teaching hospital with ear discharge and other symptoms and signs of CSOM. Results: Unilateral infection is more common 82 (65.6%) than bilateral and mostly affects lower socio-economic conditions 90 (72 %). The single bacterial isolate was seen in 102 (81.6%) cases. The mixed growth (contamination) was observed in 12 (9.6%) cases, The 11 (8.8%) cases were found sterile. Higher sensitivity (75%- 95%) was observed with cefuroxime (76.6%), piperacillin/tazobactam (78.7%), doxycycline (85.1%), amikacin (89.4%), and moxifloxacin (93.6%). It showed 38.3% sensitivity with ampicillin, 55.3% with ciprofloxacin, and 61.7% with macrolides. Levofloxacin (85.1%) was more sensitive than ciprofloxacin. Conclusions: Evaluation of microbiological pattern and their antibiotic sensitivity pattern in local area become helpful in prescribing empirical antibiotics for successful treatment of otitis media and thus minimizing its complications and emergence of resistant strains. Background: Nasal obstruction is a common cause of marked nasal septal deviation. It is related strongly with hypoxia. Hypoxic conditions increase mean platelet volume levels. Many studies in literature point out that inflammation related to nasal polyp is mostly dependent on eosinophils and their inflammatory products. Beside eosinophils, platelets may have a role in nasal polyp development. Platelets are involved in hemostasis, tissue repairing and inflammation. Recently, mean platelet volume (MPV) was recognized as a simple inflammatory marker in the inflammatory disease. This study investigated the relationship of nasal polyps with MPV (mean platelet volume), platelet count and NLR (neutrophil to lymphocyte ratio). Methods: The cross-sectional observational study we investigated CBC (complete blood count) parameters of the patients that consulted ENT clinic in a tertiary care teaching hospital, Haldia because of nasal polyp. About 76 patients and 42 controls were included in this study. In all groups, WBC (white blood cell count), RBC (red blood cell count), RDW (red cell distribution width), platelet count, MPV, PDW (platelet distribution width) and NLR parameters from CBC (complete blood count) were compared between patients and controls. Results: Mean WBC values were 6.89±1.33×103/μL in patients with NPs, vs. 7.11±2.32×103/μL in the control group. Mean haemoglobin (Hb) values were 13.19±1.34 g/dL in patients with NPs, vs. 14.1±1.67 g/dl in the control group. Mean MPV values were 9.11 ± 1.08 fL in patients with NPs, vs. 8.32±0.53 fL in the control group. Mean PLT values were 232.38 ± 39.97×103/μL in patients with NPs, vs. 271.44±45.14×103 in the control group. MPV was higher in nasal polyp patients, whereas platelet count was higher in controls. The difference was significant for the mean absolute neutrophil, platelet count, and lymphocyte counts, NLR, PDW and MPV values between the study group and the control group. <span style="font-size: 11.0pt; line-height: 115%; font-family: ’Calibri’,’sans-serif’; mso-fareast-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-IN">Conclusions:<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Calibri’,’sans-serif’; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-IN">Platelet count and NLR were significantly lower in patients than the controls, whereas MPV was significantly higher in nasal polyp patients<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Calibri’,’sans-serif’; mso-fareast-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-IN">.